Ekofilosofi "Deep Ecology" Pandangan Ekosentrisme terhadap Etika Deep Ecology - Siti Sarah; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
The purpose of this study is to discuss ecocentrism's view of deep ecology ethics. The method used in this research is qualitative through literature study. The results and discussion of this research is that the environmental crisis is motivated by a fundamental error in a philosophical understanding or view of life about human nature, nature and human position in all ecosystems. The solution can be approached not only technically and partially, but more holistically by changing the perspective and nature of human behavior radically, which must comply with environmental ethics. The conclusion of this study is that the philosophy of deep ecology emphasizes the importance of respecting biodiversity and treating nature with empathy and understanding the relationship between nature and human survival.